Breed evaluation and characterisation work in the Gambia - Agyemang, K. (International Livestock Centre for Africa, 1992)
Presents the summary of livestock breed evaluation and characterisation work in the Gambia. Discusses the on-farm work undertaken by the European Economic Community (EEC), which was intially executed jointly with International Livestock Center for Africa (ILCA) and International Laboratory for Research on Animal Diseases (ILRAD) and later (during 1991) by ILCA. The ILCA/ILRAD project conducted research to support work undertaken by the LDP. Discusses the major objectives of the Livestock Development Project (LDP), that is to evaluate the productivity of N'Dama cattle, subjected to varying levels of disease risk, under village conditions. Discusses also milk production, growth and reproduction traits, disease resistance and carcass characteristics of N'Dama cattle in The Gambia.